Sobre la superestabilidad en Q-Clases elementales abstractas (2020)
In the present work we study the concept of Q-abstract elementary class and we do an approximation to superestability in this context, adapting Shelah-Villaveces theorem. With the help of this theorem and based on chapter 15 of [Bal09], we studied the saturation of the union of chains of saturated as a weak notion of superstability.